Ethnomathematical Exploration of the Wiwitan Methik Pari Ritual Culture - Hidayah, Siti Khotimatul; Lutfiyah, Lutfiyah; Marsidi, Marsidi (ETDC: Indonesian Journal of Research and Educational Review, 2025)
The Wiwitan ritual is an agrarian tradition performed before the harvest as an expression of gratitude to God and ancestors. In its implementation, this ritual contains various cultural practices that contain mathematical concepts, such as patterns, geometric shapes, and measurements. Therefore, this study is geared toward investigating the ethnomathematic elements contained in the Wiwitan metik pari ritual culture in Umbulsari, Jember. A qualitative approach with ethnographic methods was used to uncover the meaning and practices of mathematics integrated into the ritual activities. Data were collected through participatory observation, in-depth interviews with traditional leaders and residents, and visual documentation. The findings indicate that local mathematical concepts, passed down from generation to generation, are present in the processes of preparing offerings, arranging the ritual venue, and determining the timing of implementation. These findings indicate that local culture can be a contextual learning resource that enriches mathematics learning in schools. This study recommends the integration of ethnomathematic values in the curriculum to strengthen cultural identity while increasing the relevance of mathematics learning.